Pembentukan tasawur dan kesan terhadap pembangunan tradisi keilmuan Islam - Mohd Shukri Hanapi, (Universiti Kebangsaan Malaysia, 2012)
This article attempts to discuss the origins of which led to the formation of an Islamic worldview from its grassroots. Islamic worldview has proclaimed by Rasulullah SAW in beginning of era Makkiyyah and Madaniyyah through the delivery of revelation of Allah SWT. Started from there, it has evolved from one stage to another stage until successfully built a strong tradition of Islamic scholarship. The questions raised are, how the Islamic worldview is formed in a relatively long period of time which is about 23 years? What is the effect of the formation of the Islamic knowledge traditions? To answer both of these questions, this article discusses the following three parts. First, to examine the formation of the Islamic worldview. Second, to look at the structure of knowledge formation in the Islamic worldview. Third, to analyze the development of traditional Islamic sciences as a result of the existence of knowledge structures in the Islamic worldview. It is created by focusing the discussion on prominent views of Muslim scholars. All of these views are based on the existing studies. Finally, this article concludes that the development of traditional Islamic sciences is the result of the worldview formation through a revelation by Allah SWT.